Examining Relationships between Metabolism and Persistent Inflammation in HIV Patients on Antiretroviral Therapy. (27th September 2018) - Ahmed, Duale; Roy, David; Cassol, Edana
Abstract : With the advent of antiretroviral therapy (ART), HIV-infected individuals are now living longer and healthier lives. However, ART does not completely restore health and treated individuals are experiencing increased rates of noncommunicable diseases such as dyslipidemia, insulin resistance, type 2 diabetes, cardiovascular disease, and nonalcoholic fatty liver disease. While it is well known that persistent immune activation and inflammation contribute to the development of these comorbid diseases, the mechanisms underlying this chronic activation remain incompletely understood. In this review, we will discuss emerging evidence that suggests that alterations in cellular metabolism may play a central role in driving this immune dysfunction in HIV patients on ART.